Re‐infection of Toxoplasma gondii after HSCT presenting lymphadenopathy resembling recurrence of lymphoma. Issue 3 (19th April 2018) - Hashiguchi, Junichi; Onozawa, Masahiro; Naka, Tomoaki; Hatanaka, Kanako C.; Shiratori, Souichi; Sugita, Junichi; Fujimoto, Katsuya; Matsuno, Yoshihiro; Teshima, Takanori
Abstract: Toxoplasma gondii ( T. gondii ) reactivation is one of the fatal complications after hematopoietic stem cell transplantation (HSCT); however, re‐infection has not been reported. Here, we report a case of mycosis fungoides in which cervical lymphadenopathy developed after HSCT. Initially, recurrent lymphoma was suspected. However, biopsy of the lymph node showed typical histology of toxoplasmosis and serology showed re‐infection of T. gondii . Toxoplasmosis needs to be differentiated for cases with lymphoadenopthy after HSCT.